How Binding Is Supervisory Guidance? : Evidence from the European Calendar Provisioning - Fiordelisi, Franco; Lattanzio, Gabriele; Mare, David S. (World Bank, Washington, DC, 2022)
This paper investigates whether banks respond differently to supervisory guidance than to specific regulatory action. Using a sample of subsidiaries of European banks operating in developing countries, the study exploits the sequencing in the supervisory and regulatory implementation of a reform on provisioning for credit losses for identification, generally referred to as European calendar provisioning. While the reform achieved the intended goal of reducing European banks’ nonperforming loan ratios, its effects were greater during the initial implementation of the supervisory guidance than after its enactment as a binding regulation. This finding is consistent with the notion that the subsequent formalization of the supervisory initiative within a regulatory framework achieved limited results because it eliminated the flexibility the regulatory authority had concerning the stringency with which European calendar provisioning was enforced. Finally, the study offers evidence of a mechanism through which policies in advanced economies affect banking outcomes in developing countries to which their local financial authorities should be alert.